2023
DOI: 10.1186/s13244-023-01433-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute abdominal pain in women of reproductive age: keys to suggest a complication of endometriosis

Abstract: Although endometriosis is a common gynecological condition in women of reproductive age, a complication of endometriosis is rarely considered as the differential diagnosis of acute abdominal pain in that context. However, acute events in women with endometriosis can represent life-threatening conditions, which require emergent treatment and often surgical management. Mass effect of endometriotic implants can give rise to obstructive complications, specifically occurring in the bowel or in the urinary tract, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Abdominal CT scans are typically employed as the primary imaging modality when women present to the emergency room with acute abdominal pain, aiming to facilitate the initial evaluation. However, diagnosing ruptured endometrioma can be challenging due to the nonspecific nature of CT findings [ 42 ]. In a prior study, it was reported that ruptured endometriomas exhibited an average diameter of 7 cm and displayed a multilocular structure with thicker walls in comparison to functional cysts [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal CT scans are typically employed as the primary imaging modality when women present to the emergency room with acute abdominal pain, aiming to facilitate the initial evaluation. However, diagnosing ruptured endometrioma can be challenging due to the nonspecific nature of CT findings [ 42 ]. In a prior study, it was reported that ruptured endometriomas exhibited an average diameter of 7 cm and displayed a multilocular structure with thicker walls in comparison to functional cysts [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common acute complications of endometriosis have an intestinal aetiology, such as obstruction, perforation, and acute appendicitis caused by endometriosis fibrotic implants. Other acute endometriosis manifestations include endometrioma ruptures, endometrioma superinfection, PID with tubo-ovarian abscess, and urinary tract obstruction [57][58][59][60]. MRI is considered the reference standard imaging modality for the diagnosis of endometriosis [61,62].…”
Section: Endometriosismentioning
confidence: 99%
“…In the case of gastrointestinal or urinary tract complications in an emergency setting, endometriosis is rarely identified as an aetiologic factor on imaging, even if it should be suspected in the context of known endometriosis with intestinal or urinary tract involvement. The presence of stellar, mildly enhanced, infiltrative, and fibrotic lesions in suggestive areas in female patients of reproductive age may help doctors reach the correct diagnosis [57,58]. During MRI, the presence of a hyperintense area on T1-weighted fat-saturated sequences within the lesion can suggest the diagnosis of endometriosis [44].…”
Section: Endometriosismentioning
confidence: 99%
See 1 more Smart Citation